Experimental Investigation of Forchheimer Coefficients for Non-Darcy Flow in Conglomerate-Confined Aquifer. (3rd December 2018) - Zhang, Tong; Zhao, Yixin; Gan, Quan; Yuan, Liang; Zhu, Guangpei; Cai, Yongbo; Cao, Bao
Abstract : A conglomerate-confined aquifer (CCA) plays an important role in affecting the safety and environmental protection during energy mining. In this study, the Forchheimer coefficients and associated seepage characteristics of the CCA were studied for different hydrogeological conditions via integrating theoretical analysis, hydromechanical experiment, and field investigation. Empirical models related to the intrinsic permeability (k ) and inertial resistance (β ) were developed based on theoretical and experimental solutions, governed by the parameters of particle size, initial porosity, and stress. The non-Darcy flow was obtained through experiments conducted with different ratios of the aggregate particle subjected to stress ranging from 1.43 MPa to 4.38 MPa, and a discharge model associated withk andβ was proposed. The aggregate particle and filling material of the CCA presented positive and negative effects on the interconnected pores, respectively, accompanied by wedging and wall effects. Distribution state of the aggregate particle and the filling material was affected by the stress, resulting in the reduction of the hydraulic conductivity and the weakening of the wedging and wall effects in the CCA. In addition, the transportation effect and broken effect occurred for the lower and higher stress situations and contributed to the shrinkage of the interconnected pores. Finally, the models of the CCA were validated using a normalized objective function (NOF), a linear slopeγ function, and field measurements.